DETERMINANTS OF CUSTOMER LOYALTY IN MURNI TEGUH HOSPITAL IN BALI - Leviana Aurellia Valeriant; Dewi Sri Surya Wuisan (RADJA PUBLIKA, 2025)
This research was conducted on patients at Murni Teguh Hospital Tuban Bali to find out whether price fairness and service quality have an influence on customer loyalty through customer satisfaction. The main reason this research was conducted was to find out whether these factors contributed to the positive assessment of patients towards the Teguh Tuban Bali Murni Hospital. This research is qualitative in nature with the data collection technique used is a questionnaire, with a sample size of 330 respondents, the data analysis technique used is PLS-SEM using the SmartPLS statistical application. The research results show that price fairness and service quality have a significant and positive effect on customer satisfaction. Apart from that, it was also found that price fairness, service quality and customer satisfaction have a significant and positive effect on customer loyalty.